Preventive Measures Against Non-Performing Loans: Implementation of Prudential Principles in the Buy Now Pay Later (BNPL) Scheme Through Bank–E-Commerce Partnerships - Siti Nurhasanah; Dewi Septiana; Kasmawati Kasmawati (Journal of Law and Economics, 2025)
The financial sector in Indonesia has seen a very fast change to using digital technology. This has made it possible to have Buy Now Pay Later (BNPL) services where people can get money without needing credit cards. Banks that work with online shopping companies use BNPL plans to help more people use their financial services. However, these types of partnerships also bring large dangers: bad loans build up, moral hazard appears, and there are questions about the rules. We look at how legal systems and careful management rules work in BNPL partnerships through regular legal research methodology, studying law provisions and idea bases. Law No. 7/1992, changed by Law No. 10/1998 on Banking, sets out careful needs that OJK puts into action through Regulations No. 18/ POJK.03/2016, No. 40/POJK.03/2019, No. 12/POJK.03/2021, and Circular Letter No. 34/SEOJK .03/2016 Banks put into practice careful standards by checking digital credit worthiness managing joined risks watching assets and checking partners from time to time Yet big problems stay: banks and platforms cannot share data easily regulatory power breaks up among many agencies and following the rules culture is still weak Careful ideas do more than meet rule needs they form the legal-ethical base that keeps public trust and financial safety Achieving good practice needs OJK Bank Indonesia and Kominfo to work together in their control actions guard consumers and make good digital money innovation possible.